(untitled) (Journal of Comparative Social Work, 2010)
This article aims at describing social problems we find in the Russian Army. The research has allowed us to get a ranging of servicemen`s social problems: housing, material maintenance and hard-earned money, realization of social guarantees, life conditions and problem of relationships within families, time-limit, the regulation of life, restricting the freedom, humiliating treatment of juniors and bullying. Unsolved social problems of servicemen may also cause that people who are going to protect the country from danger, may become threats themselves. The Russian army consumes a great amount of resources. Recently mass media has put these issues on the public agenda. Focus in article is also to give a picture of how social workers work to solve social problems in the Russian Army.